Forest products and rural households: woodcraft commercialisation in Southern Zimbabwe - Braedt, O. (Kommissionsverlag, Buchhandlung Max Wiedebusch, 2003)
The focus of this thesis is to assess the importance and potential of forest products for the sustainable development of tropical rural areas and, specifically, the role of forest product commercialisation for rural households. By using the example of woodcraft sector the book reveals aspects which need to be addressed in order to achieve sustained income from forest product commercialisation. The study concludes that there is little ecological and silvicultural information regarding communal area forests to inform the policy development process in regard to woodcraft sector in Zimbabwe. Macroeconomic policies, forestry regulations, certification efforts, and the creation of market information systems are some aspects that need to be addressed so that forest product dependent livelihoods can be secured. Three aspects to be considered to sustain the flow of income obtained through the commercialisation of forest products: (1) legal contradictions which relate to woodcraft production and sale, (2) the formal recognition and incorporation of the sector, and (3) the provision of the alternative wood supplies.